Effects of Displaced Reference Points on Deformation Analysis - Aydin, Cuneyt (ASCE-AMER SOC CIVIL ENGINEERS, 2017)
The geodetic datum of a deformation monitoring network is defined using its reference points. This article discusses how deformation analysis is affected when reference points have been displaced as a result of rigid body displacement (translation and rotation) and deformation (extension or contraction) of the reference block; this article also includes points with single-point displacements. With this aim, the effects of the displacements of the reference points on the estimated displacements of the network points are considered. The well-known similarity (S)-transformation matrix associated with network datum is a convenient projector for explaining these effects. Some horizontal and vertical monitoring network examples are used to discuss the effects of the displaced reference points on deformation analysis.
Keywords: Deformation analysis; Reference points; Displacement; Monitoring network; NETWORKS; STRAIN; Engineering